Ice petrofabrics, Tuktoyaktuk, N.W.T., Canada ... - Gell, Alan William (University of British Columbia, 2011)
This thesis attempts to elucidate the origin and deformation of a folded sequence of ice and icy sediment in Tuktoyaktuk, N.W.T., Canada. Tuktoyaktuk lies between the maximum and late Wisconsin limits of glaciation. Bodies of underground ice in permafrost have characteristic ice crystal sizes and shapes and inclusions dependent on the mode of ice growth and subsequent deformational or other history. The ice body which was studied lies beneath 2 m of fluvioglacial sands and 0.6 m of gravel. The ice-icy sediment foliation has been deformed into subhorizontal isoclinal folds, the major movement being from the SSW. Folds are classified into three styles. Fabric diagrams of ice crystal optic axes are of two types. A relict early fold shows a cleft girdle pattern at right-angles to the fold axis. Later flattening and fold limb extension has given rise to fabric diagrams with strong maxima normal to the axial surfaces, showing that crystals have rotated such that slip planes are parallel to the surface of slip of ...